Structure of the red-shifted Fittonia albivenis photosystem I - Li, Xiuxiu; Huang, Guoqiang; Zhu, Lixia; Hao, Chenyang; Sui, Sen-Fang; Qin, Xiaochun (Nature communications, 2024)
Photosystem I (PSI) from Fittonia albivenis , an Acanthaceae ornamental plant, is notable among green plants for its red-shifted emission spectrum. Here, we solved the structure of a PSI–light harvesting complex I (LHCI) supercomplex from F. albivenis at 2.46-Å resolution using cryo-electron microscopy. The supercomplex contains a core complex of 14 subunits and an LHCI belt with four antenna subunits (Lhca1–4) similar to previously reported angiosperm PSI–LHCI structures; however, Lhca3 differs in three regions surrounding a dimer of low-energy chlorophylls (Chls) termed red Chls, which absorb far-red beyond visible light. The unique amino acid sequences within these regions are exclusively shared by plants with strongly red-shifted fluorescence emission, suggesting candidate structural elements for regulating the energy state of red Chls. These results provide a structural basis for unraveling the mechanisms of light harvest and transfer in PSI–LHCI of under canopy plants and for designing Lhc to harness longer-wavelength light in the far-red spectral range. Fittonia albivenis is shade-adapted ornamental plant that can efficiently use far-red light for photosynthesis. Here the authors describe the structure of the red-shifted F. albivenis photosystem I to give insights into how plants can use far-red light to drive photochemistry.